International audit of Virtual Environment for Radiotherapy Training usage. Issue 4 (14th November 2017) - Bridge, P.; Giles, E.; Williams, A.; Boejen, A.; Appleyard, R.; Kirby, M.
Abstract: Introduction: The Virtual Environment for Radiotherapy Training (VERT) is a high-fidelity simulation hardware and software resource that replicates the expensive and high-pressure clinical environment of a radiotherapy treatment machine. The simulation allows students to gain confidence with clinical techniques in a safe and unpressured academic environment before clinical placement. The aim of this study was to establish the current and future role of VERT and explore the potential for collaborative resource development and research. Methods: An anonymous online survey was made available to all users of the software internationally ( n =52). A mixture of fixed and open response questions gathered usage data and user feedback. Results: The study had a 90% response rate ( n =47). Most participants (78·5%) used the resource 1 day/week or less; around 8, 000 hours worldwide. It was clear that most participants used the simulation resource to help student to either gain understanding of concepts and techniques or to gain practice with techniques and practical skills. There was good support for collaborative resource development, deployment and evaluation to help VERT users to fully exploit its range of pedagogical uses. Conclusions: This audit demonstrated high levels of engagement and enthusiasm for collaborative resource development and ongoing research among the radiotherapy simulation community. Adoption of an international Academic Community of Practice for collaborative simulation resource deployment and support may be of significant value and is worthy of further discussion and consideration.